2009
DOI: 10.1073/pnas.0902827106
|View full text |Cite
|
Sign up to set email alerts
|

Surviving mass extinction by bridging the benthic/planktic divide

Abstract: Evolution of planktic organisms from benthic ancestors is commonly thought to represent unidirectional expansion into new ecological domains, possibly only once per clade. For foraminifera, this evolutionary expansion occurred in the Early-Middle Jurassic, and all living and extinct planktic foraminifera have been placed within 1 clade, the Suborder Globigerinina. The subsequent radiation of planktic foraminifera in the Jurassic and Cretaceous resulted in highly diverse assemblages, which suffered mass extinct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
53
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 45 publications
0
53
0
Order By: Relevance
“…In our case, the hypothesis of eutrophic waters seems to fit better, because an important planktonic bloom was recorded only subsequently, related to the advancing Middle Miocene transgression. Darling et al (2009) used the term "tychopelagic" to describe organisms that usually live as benthos but can survive and grow in fairly large numbers as plankton and may be advected well offshore into open ocean assemblages. They revealed that tychopelagic Bolivina may well evolve into true pelagic forms and consequently biserials can become abundant in the planktonic assemblage at some time intervals (isotopic and distributional evidence suggest their truly pelagic life).…”
Section: Discussion and Interpretationmentioning
confidence: 99%
See 1 more Smart Citation
“…In our case, the hypothesis of eutrophic waters seems to fit better, because an important planktonic bloom was recorded only subsequently, related to the advancing Middle Miocene transgression. Darling et al (2009) used the term "tychopelagic" to describe organisms that usually live as benthos but can survive and grow in fairly large numbers as plankton and may be advected well offshore into open ocean assemblages. They revealed that tychopelagic Bolivina may well evolve into true pelagic forms and consequently biserials can become abundant in the planktonic assemblage at some time intervals (isotopic and distributional evidence suggest their truly pelagic life).…”
Section: Discussion and Interpretationmentioning
confidence: 99%
“…The internal plate that connects succeeding apertural borders does not project freely into the aperture as a tooth plate (as in the case of Bolivinitidae). Recent genetic work has shown that the planktonic S. globigerus and the benthic B. variabilis are the same biological species (Darling et al 2009). Regardless of the taxonomic problem (Streptochilus or Bolivina), the presence of abundant biserial taxa gives a new approach to the paleogeographic and biostratigraphic interpretations.…”
Section: Biserial Foraminiferal Assemblagesmentioning
confidence: 99%
“…In a recent issue of PNAS, Darling et al (2) provide compelling evidence to further support the polyphyletic hypothesis, while also demonstrating a very peculiar dual mode of life for one particular species of foraminifer. Here, for the first time, Darling et al conclusively demonstrate that the benthic Bolivina variabilis and planktic Streptochilus globigerus are one and the same species.…”
mentioning
confidence: 91%
“…Guembelitria survived the end-Cretaceous mass extinction and gave rise to several microperforate genera during the Paleocene (25). One group that may be similar to Bolivina/ Streptochilus, described by Darling et al (2), is Zeauvigerina, another survivor of the Cretaceous-Paleogene boundary. These taxa also resemble benthic taxa, but they have stable isotopic values that are equivocal regarding a benthic or planktic mode of life (23).…”
mentioning
confidence: 99%
See 1 more Smart Citation